Mycobacterium tuberculosis: here today, and here tomorrow - Russell, David G. (Nature reviews. Molecular cell biology, 2001)
Key Points Pathogenic Mycobacterium spp. survive within the macrophages of their host. One of these, Mycobacterium tuberculosis , is a highly successful pathogen that subverts two pathways of its host. First, it stops the normal progression of the phagosome into an acidic, hydrolytically active compartment; and second, it avoids the development of a localized, productive immune response that could activated the host cell. The bacilli gain entry to macrophages through binding to one of several phagocytic receptors. Once in the cell, Mycobacterium are retained in a phagocytic vacuole until the host cell dies by necrosis or apoptosis. These vacuoles fail to fuse with lysosomes, but they remain fusion-competent, acquire some 'lysosomal' proteins from the synthetic pathway of the host cell, and undergo fusion with other vesicles of the endosomal system.We are beginning to understand the molecular mechanisms that Mycobacterium use to prevent maturation of the phagosomes after uptake by the macrophage. Host cells have also developed means of protection against intracellular parasites such as Mycobacterium . For example, NRAMP1 ( natural-resistance-associated macrophage 1) confers innate resistance for macrophages against the growth of certain intracellular microorganisms, and might influence vacuolar pH. It is hoped that new genetic screens will shed light on the molecules that Mycobacterium uses to maintain the host as a habitable environment. Mycobacterium avoid or minimize the induction of a productive immune response and suppress the effector cascade once such a response has developed. It is thought that mycobacteria do this by sequestering vacuoles away from the normal antigen-processing and -presentation machinery, and by modulating the environment in the immediate vicinity of the infected macrophage. Understanding the position of infected vacuoles in the endosomal pathway should help us to develp improved drug delivery. For this, a much greater understanding of the endosomal-lysosomal environment is required. Mycobacterium tuberculosis is a highly successful pathogen that parasitizes the macrophages of its host. Its success can be attributed directly to its ability to manipulate the phagosome that it resides in and to prevent the normal maturation of this organelle into an acidic, hydrolytic compartment. As the macrophage is key to clearing the infection, the interplay between the pathogen and its host cell reflects a constant battle for control.